Estetika fragmenta kot ključ za razumevanje Schumannove Hausmusik - Bogunović Hočevar, Katarina (Muzikološki zbornik, 2007)
Schumann's music - especially the music composed until approximately 1840 - is today regarded as a paradigm of romantic instrumental music. The composer's enthusiasm for the romantic literature of his time did not remain simply on the level of reception and isolated literary experiments, it strongly influenced his musical poetics. Without a knowledge of the aesthetic of the (literary) fragment, however, the latter remains merely a field of numerous interpretive gaps.
Keywords: estetika fragmenta; klavirska glasba; romantična estetika; samospevi; Schumann, Robert, 1810-1856; Schumann, Robert: Hausmusik